2014
DOI: 10.1162/jocn_a_00546
|View full text |Cite
|
Sign up to set email alerts
|

Commonalities for Numerical and Continuous Quantity Skills at Temporo-parietal Junction

Abstract: Abstract■ How do our abilities to process number and other continuous quantities such as time and space relate to each other? Recent evidence suggests that these abilities share common magnitude processing and neural resources, although other findings also highlight the role of dimension-specific processes. To further characterize the relation between number, time, and space, we first examined them in a population with a developmental numerical dysfunction (developmental dyscalculia) and then assessed the exte… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

3
20
2

Year Published

2014
2014
2024
2024

Publication Types

Select...
7
2

Relationship

1
8

Authors

Journals

citations
Cited by 26 publications
(25 citation statements)
references
References 53 publications
(87 reference statements)
3
20
2
Order By: Relevance
“…Several findings support the theory of a generalized magnitude system, although contradictory results speaking for a partial overlap or separate magnitude systems are also found (Cappelletti et al, 2014). …”
Section: Introductionmentioning
confidence: 63%
“…Several findings support the theory of a generalized magnitude system, although contradictory results speaking for a partial overlap or separate magnitude systems are also found (Cappelletti et al, 2014). …”
Section: Introductionmentioning
confidence: 63%
“…Interestingly, some studies demonstrated that mathematical abilities do not correlate with specific computations: size and density sensitivity do not correlate with math, in contrast to visual numerosity (Anobile et al, 2016(Anobile et al, , 2018. Similarly, average size (Castaldi et al, 2018), line length (Cappelletti et al, 2014;De Visscher et al, 2017) and area (Iuculano et al, 2008) are not impaired by dyscalculia, a learning deficit affecting number processing. The evidence that numerical concepts can be acquired in CB raise the question as to whether these perceptual factors that link to the development of arithmetic abilities in the sighted are independent from visual experience or whether, in contrast, CB people rely on separate perceptual processes in order to develop adequate arithmetic abilities through separate cognitive mechanisms (Dormal et al, 2016b; Crollen et al, 2017).…”
Section: Discussionmentioning
confidence: 99%
“…Based on this model, number and duration discrimination rely on a single magnitude system which operates in either the counting or the timing mode (Fetterman, 1993). From an experimental perspective, a number of behavioral (Alards-Tomalin, Walker, Kravetz, & Leboe-McGowan, 2016;Cappelletti, Freeman, & Butterworth, 2011;Cappelletti et al, 2009;Chun, Lee, Lee, & Cho, 2018;Dormal, Seron, & Pesenti, 2006;Gilaie-Dotan, Rees, Butterworth, & Cappelletti, 2014;Javadi & Aichelburg, 2012;Lambrechts, Walsh, & Van Wassenhove, 2013;Martin, Wiener, & Van Wassenhove, 2017;Tokita & Ishiguchi, 2011;Tsouli, Dumoulin, te Pas, & van der Smagt, 2019) and neuroimaging (Bueti & Walsh, 2009;Cappelletti et al, 2014;Castelli, Glaser, & Butterworth, 2006;Hayashi et al, 2013;Javadi, Brunec, Walsh, Penny, & Spiers, 2014) studies provide support for a partly shared processing system for numerosity and time, whereas other studies suggest that numerosity and time are independent and are processed by distinct mechanisms (Agrillo, Piffer, & Adriano, 2013;Agrillo, Ranpura, & Butterworth, 2010).…”
Section: Introductionmentioning
confidence: 99%